Las técnicas gráfico-esquemáticas como estrategia metacognitiva y desempeño académico de los estudiantes de la Universidad Católica sede Sapientiae - Romero Díaz, Alejandra Dulvina (2022)
The purpose of this research was to determine the degree of relationship between graphic-schematic techniques as a metacognitive strategy on academic performance. The sample consisted of 54 students from the Faculty of Education of the Catholic University Sedes Sapientiae. For this purpose, the quasi-experimental approach was used and the results were processed with the SPSS version 12 statistical package. After the application of workshops for learning the graphic-schematic techniques as a metacognitive strategy, the evaluation of the levels of academic performance and a survey on the personal appreciation of each of them were carried out. The study concluded in the positive perception of the aforementioned techniques and their tangible effect on academic performance. The statistical study finally confirmed the close and positive relationship between the variables under study.